A multianalytical approach for identifying a manganese source for the black pigment of the Chinchorro mortuary palette. Issue 3 (16th December 2018) - Van Hoesen, John; Arriaza, Bernardo; Ryan, Peter; Grady, C.
Abstract: The primary goal of this study was to characterize and evaluate the potential origins of manganese‐based paint used to decorate the Chinchorro mummies of northern Chile. We sampled small painted fragments from the trunk of two black mummies and nine samples from the cranium/face of the red mummies. In addition, we sampled manganese‐bearing rocks from the Lauca and Huaylas Formations exposed in the Altiplano, approximately 80–90 km northeast of Arica, Chile. Using scanning electron microscopy, energy‐dispersive spectroscopy, X‐ray diffraction, inductively coupled plasma mass spectrometry, and oxygen isotopic data, we propose these two formations are the likely source of manganese used by the Chinchorro culture to create their distinctive mortuary paint. However, the processes by which they collected and transported the raw material are still unclear. It is possible that Chinchorro traveled to the Altiplano, but a more likely cost‐benefit scenario is that manganese‐rich clasts were transported to lower elevations via rivers fed by seasonal rain and snowmelt.